SACRED MYTHS OF THE CEREKANG INDIGENOUS COMMUNITY: LOCAL WISDOM STRATEGIES FOR ENVIRONMENTAL PRESERVATION - Hadrawi, Muhlis; Sherira, Sherira; Bachrong, Faizal; Agus, Nuraidar; Yusuf, Yusuf; Syamsuriah, Syamsuriah; binti Daeng Jamal , Daeng Haliza (Balai Penelitian dan Pengembangan Agama Makassar, 2025)
This article examines the sacred myths upheld by the Cerekang Indigenous Community, conceptualized through ideas of